Corporate Social Responsibility (CSR) Dalam Perspektif Undang-undang Nomor 40 Tahun 2007 tentang Perseroan Terbatas - NUR ARIFUDIN (Fakultas Hukum Universitas Mulawarman, 2008)
Corporate Social Responsibility (CSR) constitutes a commitment in the limitedcompany or business world to give a contribution to sustainable economic rate forimmediate community as well as to take the responsibility of the balance betweeneconomic, social, and environment through ethic and moral considerations. Suchconsideration may be evident as written in an article of Undang-undang Nomor 40Tahun 2007 tentang Perseroan Terbatas. The complexity challenging Indonesian seemsawful in the recent years. CSR pumps out a little hope to become a concept withbreakthrough alternative in dealing with poverty through limited companysupported by reliable legislations.Key words: tanggung jawab sosial dan lingkungan (social and environment responsibility),perseroan (corporate), keseimbangan (balance)